TENCON 2017 - 2017 IEEE Region 10 Conference 2017
DOI: 10.1109/tencon.2017.8228233
|View full text |Cite
|
Sign up to set email alerts
|

Drawing guessing game for the elderly

Abstract: Abstract-Drawing guessing game is the game where the users are required to guess the item that is progressively drawn on the screen. In this project, an elderly oriented mobile drawing guessing game named Guess It was developed. This application allows the drawings to be added into the cloud database from time to time and get downloaded to the user's mobile devices without the need to update the application. The time taken to complete each game can be recorded to monitor the progress of the elderlies who plays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…With technologies improvements and affordable price of mobile devices, the researchers on mobile gaming for elderly are mushrooming [7], [8]. Studies showed that mobile gaming can increase the cognitive abilities of elderly at the same time give the elderly sense of enjoyment and reduce the feeling of loneliness.…”
Section: Introductionmentioning
confidence: 99%
“…With technologies improvements and affordable price of mobile devices, the researchers on mobile gaming for elderly are mushrooming [7], [8]. Studies showed that mobile gaming can increase the cognitive abilities of elderly at the same time give the elderly sense of enjoyment and reduce the feeling of loneliness.…”
Section: Introductionmentioning
confidence: 99%